LITERATURE AND MEMORY AS a BEACON TO THE READER: AN ANALYSIS OF AINDA ESTOU AQUI, BY MARCELO RUBENS PAIVA - Ferreira, Eliane Aparecida Galvao Ribeiro [UNESP]; Bulhoes, Ricardo Magalhaes; Burgo, Vanessa Hagemeyer (Univ Federal Santa Maria, 2022)
This article aims to present a reflection on the importance of meaning effects (ISER, 1996, 1999) that Marcelo Rubens Paiva's mastery produces in the management of the potentialities of lan-guage in his autobiographical novel Ainda estou aqui (2015). We intend, more specifically, to observe how Paiva (2015), by using hybrid literary discourse, guided by figurative language, by emotions and metaphors, but also by interweaving documents, testimonies, among other textual genres, can bring his narrative closer to readers, encouraging critical reviews of history. Based on the theoretical framework of Aesthetic of Reception (JAUSS, 1994; ISER, 1996, 1999), we hypothesize that his work confronts the contemporary reader, ensuring communicability.
Keywords: Military dictatorship; memorial novel; social function of literature